Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen PT JNE Cabang Latta Ambon - Chiska Edelweis Hahury; Ambarwati Soetiksno; Saul Saleky (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the factors influencing customer satisfaction at PT JNE Cabang Latta Ambon, focusing on five dimensions of service quality according to the SERVQUAL model: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Data were collected through a questionnaire distributed to 145 respondents using shipping services. The results of the analysis indicate that of the five dimensions, only the Empathy dimension has a positive and significant effect on customer satisfaction (β = 0.204; p = 0.048). The other variables, while showing positive effects, did not demonstrate statistical significance. The regression model developed was able to explain approximately 22.1% of the variation in customer satisfaction, emphasizing that there are other factors beyond the measured dimensions that also influence satisfaction. The F-test results show that, simultaneously, all five dimensions of service quality significantly affect customer satisfaction, supporting the SERVQUAL theory that highlights the importance of a multidimensional approach in service delivery. Practical implications of this study suggest that PT JNE Latta Ambon should focus more on enhancing empathy and responsiveness in service, while maintaining the quality of other aspects as a minimum standard. This research provides valuable insights for developing more effective customer-oriented service strategies and opens opportunities for further research in this field.